Revisit of Tunisia’s Money Demand Function: What About Oil Price and Exchange Rate Effects? - Neifar, Malika; Kammoun, Niazi (International Journal of Economics and Financial Issues, 2022)
This paper examines the long run and short run dynamic relationship between real broad money and macroeconomic factors in Tunisia for the period 2010M01 to 2019M07. We employ linear and NARDL bound testing approach for co-integration between the money demand measure and its determinants. Three real broader money demand variables (M2, M3, and M4) are considered to show that exchange rate have asymmetric significant effects once we introduce nonlinearity in the long run as well as in the short run association. Then, by using the (Shin et al., 2014) NARDL approach, we show that currency appreciation and depreciation could affect the demand for money in an asymmetric manner. However, in the long run, it is only the oil price and Tunisian Dinar (TD) depreciation and appreciation which have significant effect out of the five considered macroeconomic factors (real income, interest rates, inflation, oil price, and the exchange rate). Besides, the QSUMSQ stability tests results reveal that only real M3 money demand function which is clearly stable. In implementing monetary policy, the Tunisian central bank (TCB) should target the M3 monetary aggregate and take into account of the exchange rate changes stabilization.